All Together Now - Preparing for Group Instrumental Teaching using Simultaneous Learning in and ETB Music School - Saunders, Eimear Róisín (Trinity College (Dublin, Ireland). School of Education, 2021)
This study investigates the impact of training in Simultaneous Learning on teachers’ practice and perception of small group teaching in an Education and Training Board (ETB) music school. A mixed methods approach was taken to this research and a ‘Teacher as Researcher’ methodology was employed. The intervention consisted of three training sessions based on Paul Harris’s ‘Simultaneous Learning' approach. Two training sessions were conducted in person and were one hour each in duration while the third session took the form of a training session plan which was emailed to participants due to Covid 19 related school closures. Data collection consisted of two questionnaires – one pre-intervention and one post intervention, which were completed by seven participants – and post-intervention interviews (completed by four participants). Analysis of the data showed that training in Simultaneous Learning provided participants with sufficient means to adapt their one-to-one teaching to accommodate small groups of students. Training in Simultaneous Learning also led to a change in participants’ perception of group teaching. After the intervention, a number expressed the opinion that group lessons may be more beneficial than one-to-one lessons for some students. The research supports the use of Simultaneous Learning in preparing teachers who are experienced in one-to-one teaching for group instrumental teaching. More research is required to assess the effectiveness of this approach for less experienced teachers.
Keywords: Music in Education; Education